On the concept of Urban Mutations: Urban research bibliography with an objective approach - Z. Bendebbache; A. Khiari; I. Maanser (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: Urban studies, as a field of research, often encounter a certain strictness in determining precise concept definitions. This latter represents the epistemological underpinnings which are considered as the base of their theoretical foundation. Such difficulty in pinpointing an accurate definition is particularly evident in the varying terminology used to describe urban phenomena, ranging from terms like “mutation”, “change”, “transformation”, “gentrification”, and “transition”. Each term carries its own nuances and implications, reflecting the diverse perspectives within the field. In this context, the primary objective of this paper is to evaluate scientific publications within the realm of urban studies to conduct a comprehensive analysis, assessing the frequency and contextual significance of the aforementioned terms in articles about urban mutations. METHODS: The article framework involved conducting a bibliometric review of the literature using the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses” framework. The first 5595 documents were identified in the Scopus database. After a process of inclusion and exclusion, only 1768 articles spanning from 1981 to 2023 were extracted. These data were then processed using CiteSpace to analyze cooperative networks. This analysis encompasses three key dimensions: Citation, Co-citation, and Co-occurrence.FINDINGS: Few authors used bibliometrics to address urban mutations comprising only 32 articles, published between 2016 and 2023. The citation analysis revealed Salvati Luca as the most co-cited author, and the United Kingdom as a top contributing country with 287 citations and a centrality value of 0.35. Furthermore, the co-citation analysis ranked the cluster labeled “Urban Change” at the top with 501 citations and 0.917 for silhouette. Meanwhile, the most frequently co-cited journal is “Urban Studies”, boasting 602 co-citations. For the co-occurrences, the term “Urban Change” ranked second in strength burst (35.13), and first in centrality (0.41). The term “Urban Transformation” holds the 19th position with a centrality score of 0.05. However, this latter ranks 3rd in the classification by citation (384). “Urban Change”, then, comes in at the 5th position with 211 citations. The term “Urban Mutation” did not appear in any analysis. “Urban Change” and “Urban Transformation” stand out as the most commonly used. Most references are cited in English.CONCLUSION: Scientometric analysis is essential for identifying potential correlations within the literature. This helps urban studies utilize discipline-specific terminology, thereby ensuring the rigor and integrity of its concepts. Moreover, this study could be used for other comparisons with different databases, such as Web of Science, Dimensions, and PubMed